2018
DOI: 10.1111/cgf.13356
|View full text |Cite
|
Sign up to set email alerts
|

Efficient BVH‐based Collision Detection Scheme with Ordering and Restructuring

Abstract: Bounding volume hierarchy (BVH) has been widely adopted as the acceleration structure in broad‐phase collision detection. Previous state‐of‐the‐art BVH‐based collision detection approaches exploited the spatio‐temporal coherence of simulations by maintaining a bounding volume test tree (BVTT) front. A major drawback of these algorithms is that large deformations in the scenes decrease culling efficiency and slow down collision queries. Moreover, for front‐based methods, the inefficient caching on GPU caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Wang et al . [WTMT18]). However, a degradation of BVH quality is also inevitable when accumulated deformations within dynamic scenes cause significant increases in the overlap among child bounding volumes.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al . [WTMT18]). However, a degradation of BVH quality is also inevitable when accumulated deformations within dynamic scenes cause significant increases in the overlap among child bounding volumes.…”
Section: Related Workmentioning
confidence: 99%
“…[KIS∗12] propose a well‐related incremental update scheme by combining refitting with local restructuring to modify sub‐trees via rotations, and node splitting. However, they still advocate for a full rebuild when extreme degenerations occur, which has seen recent application within GPU‐based collision detection [WTMT18].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers like Wei et al and Wang et al improved the BVH methods to achieve better collision detection performance, but these methods need large storage spaces. 8,9 Some methods, proposed by Müller et al and Zou et al, can only be used for collision detection of specific models, and have limitations in application. 10 Some methods, such as GPU-based collision detection algorithm designed by Tang et al and Weller et al, showed that its performance depends on the calculation speed of GPU.…”
Section: Introductionmentioning
confidence: 99%